PENGEMBANGAN PROTOTIPE NAVIGASI AUGMENTED REALITY DENGAN FITUR PENGENALAN SUARA MENGGUNAKAN GDLC STUDI KASUS: DI LINGKUNGAN PENDIDIKAN - Khadijah Khadijah; Nur Choiriyati; Meita Sekar Rahayu (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
The rapid evolution of digital technology is transforming educational practices, enhancing accessibility and interactivity through innovations like augmented reality (AR) and artificial intelligence (AI). This study aims to develop the PDBI Tour application, an AR-based navigation tool integrated with speech recognition, to improve campus accessibility for new students and promote Politeknik Digital Boash Indonesia, a vocational education in Bogor Regency. A Game Development Life Cycle (GDLC) methodology was adopted, comprising initiation, pre-production, production, testing, beta, and release phases. Data were collected through interviews with promotional teams and prospective students, and prototype design was created using Figma, while Unity was used for production with AR Foundation and Whisper API. Functional testing (black box) confirmed reliable navigation features, and usability testing yielded a 65% satisfaction rate from 25 respondents representation of students in PDBI aged 18-20 years who had tried the prototype, highlighting effectiveness in usability, playability, and accessibility. These findings indicate that the PDBI Tour application prototype meets user needs and offers potential as an immersive navigation and promotional tool. This research demonstrates the GDLC approach’s efficacy in enhancing application development through iterative improvements, validating AR navigation as a powerful tool for interactive and accessible campus experiences.